Search for massive resonances decaying into WW, WZ, ZZ, qW, and qZ with dijet final states at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Ero,J; Flechl,M; Friedl,M; et al. (PHYSICAL REVIEW D, 2018)
Results are presented from a search in the dijet final state for new massive narrow resonances decaying to pairs of W and Z bosons or to a W/Z boson and a quark. Results are based on data recorded in proton-proton collisions at √s=13  TeV with the CMS detector at the CERN LHC. The data correspond to an integrated luminosity of 35.9  fb−1. The mass range investigated extends upwards from 1.2 TeV. No excess is observed above the estimated standard model background and limits are set at 95% confidence level on cross sections, which are interpreted in terms of various models that predict gravitons, heavy spin-1 bosons, and excited quarks. In a heavy vector triplet model, W′ and Z′ resonances, with masses below 3.2 and 2.7 TeV, respectively, and spin-1 resonances with degenerate masses below 3.8 TeV are excluded at 95% confidence level. In the case of a singlet W′ resonance masses between 3.3 and 3.6 TeV can be excluded additionally. Similarly, excited quark resonances, q∗, decaying to qW and qZ with masses less than 5.0 and 4.7 TeV, respectively, are excluded. In a narrow-width bulk graviton model, upper limits are set on cross sections ranging from 0.6 fb for high resonance masses above 3.6 TeV, to 36.0 fb for low resonance masses of 1.3 TeV.